Screening for Beta Thalassemia Trait - Raiz Ahmed Qazi , Rabia Shams , Hamid Hassan , Naghmi Asif (Journal of Rawalpindi Medical College, 2014)
Background : To evaluate the prevalence of beta thalassemia trait (BTT) among the students of schools, colleges and universities of Nawabshah city. Methods: In this descriptive cross sectional study students of schools, colleges and universities of Nawabshah were selected. The blood samples from these subjects were tested for complete blood count, and red cell indices. The microscopic examination of peripheral blood smears stained with Field’s stain was performed for the morphology of red blood cells. Serum ferritin and automated haemoglobin electrophoresis at cellulose acetate alkaline pH was performed. Subjects with microcytic hypochromic blood picture and low ferritin level were not subjected to haemoglobin electrophoresis. Results: In total of 521 subjects 65.4% were females, with female to male ratio of 1.8:1. Mean age was 17.5 years. On screening diagnosis of beta thalassemia trait was made in 4.9% cases and haemoglobin electrophoresis showed mean haemoglobin A2 of 5.8% in these cases. The microscopic examinations of peripheral blood smears among the subjects with BTT showed microcytic hypochromic red blood cells with presence of target cells. Conclusion: The prevalence of beta thalassemia BTT was 4.9%.